Heavy metal contamination in pristine environments: lessons from the Juan Fernandez fur seal (Arctocephalus philippii philippii). Issue 3 (29th March 2023) - Toro-Valdivieso, Constanza; Jugdaohsingh, Ravin; Powell, Jonathan J.; Hoffman, Joseph I.; Forcada, Jaume; Moore, Charles; Blacklaws, Barbara
Abstract : Heavy metals, including mercury (Hg) and cadmium (Cd), occur naturally or anthropogenically and are considered toxic to the environment and human health. However, studies on heavy metal contamination focus on locations close to industrialized settlements, while isolated environments with little human activity are often ignored due to perceived low risk. This study reports heavy metal exposure in Juan Fernandez fur seals (JFFS), a marine mammal endemic to an isolated and relatively pristine archipelago off the coast of Chile. We found exceptionally high concentrations of Cd and Hg in JFFS faeces. Indeed, they are among the highest reported for any mammalian species. Following analysis of their prey, we concluded that diet is the most likely source of Cd contamination in JFFS. Furthermore, Cd appears to be absorbed and incorporated into JFFS bones. However, it was not associated with mineral changes observed in other species, suggesting Cd tolerance/adaptations in JFFS bones. The high levels of silicon found in JFFS bones may counteract the effects of Cd. These findings are relevant to biomedical research, food security and the treatment of heavy metal contamination. It also contributes to understanding the ecological role of JFFS and highlights the need for surveillance of apparently pristine environments.